Zaburzenia mowy a gotowość podjęcia nauki szkolnej - Wołosiuk, Beata (Studia Edukacyjne, 2020)
Speech plays a key role in our lives. Normal development of speech is an important condition of school readiness. The article presents child’s speech development. It is focused on the speech development of a six - year - old child. The paper presents the causes of speech disorders and the most frequent speech disorders as dyslalia, stuttering and delays in speech. The article describes the term ‘school readiness’. The author explains the influence of speech disorders on child functioning in school and school difficulties.